2015
DOI: 10.1155/2015/939625
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Effect ofEquisetum giganteumL. againstCandidaBiofilm Formation: New Approaches to Denture Stomatitis

Abstract: Equisetum giganteum L. (E. giganteum), Equisetaceae, commonly called “giant horsetail,” is an endemic plant of Central and South America and is used in traditional medicine as diuretic and hemostatic in urinary disorders and in inflammatory conditions among other applications. The chemical composition of the extract EtOH 70% of E. giganteum has shown a clear presence of phenolic compounds derived from caffeic and ferulic acids and flavonoid heterosides derived from quercitin and kaempferol, in addition to styr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 48 publications
(44 reference statements)
0
49
1
4
Order By: Relevance
“…With the exception of quercetin-3-O-glucoside and kaempferol-3-O-rutinoside, reported in E. giganteum by Francescato et al 15 and Alavarce et al, 16 none of the compounds detected herein had been previously described in this species.…”
Section: Peaks 2 Eg Andcontrasting
confidence: 50%
See 3 more Smart Citations
“…With the exception of quercetin-3-O-glucoside and kaempferol-3-O-rutinoside, reported in E. giganteum by Francescato et al 15 and Alavarce et al, 16 none of the compounds detected herein had been previously described in this species.…”
Section: Peaks 2 Eg Andcontrasting
confidence: 50%
“…Based on their fragmentation features and following a similar reasoning as for the previous kaempferol derivatives, they were assigned as quercetin-di-O-glucoside and quercetin-O-acetylglucoside-O-glucoside, respectively. Peak 2 Eg was tentatively identified as quercetin-3,7-di-O-glucoside, owing to the previous description of such a compound in E. giganteum by Francescato et al 15 and Alavarce et al 16 Finally, peak 1 Eg was identified as a caffeic acid hexoside according to its UV and mass characteristics.…”
Section: Peaks 2 Eg Andmentioning
confidence: 84%
See 2 more Smart Citations
“…Bacillus species have been reported to be useful as bio-control agents against plant fungal diseases 53 . Numerous species of the Bacillus genus are reasonably considerable for the purposes, as they are functional for the production of numerous molecules and supplementary goods for foodstuff as well as in agricultural, biological and pharmaceutical industries 55,56 . In the pharmaceutical industry, there is high demand for Bacillus species because of its potential to produce a broad array of metabolites with antimicrobial activity [57][58][59][60][61] .…”
Section: Discussionmentioning
confidence: 99%